-5(t-4)+8t=5t-5

Simple and best practice solution for -5(t-4)+8t=5t-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(t-4)+8t=5t-5 equation:


Simplifying
-5(t + -4) + 8t = 5t + -5

Reorder the terms:
-5(-4 + t) + 8t = 5t + -5
(-4 * -5 + t * -5) + 8t = 5t + -5
(20 + -5t) + 8t = 5t + -5

Combine like terms: -5t + 8t = 3t
20 + 3t = 5t + -5

Reorder the terms:
20 + 3t = -5 + 5t

Solving
20 + 3t = -5 + 5t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-5t' to each side of the equation.
20 + 3t + -5t = -5 + 5t + -5t

Combine like terms: 3t + -5t = -2t
20 + -2t = -5 + 5t + -5t

Combine like terms: 5t + -5t = 0
20 + -2t = -5 + 0
20 + -2t = -5

Add '-20' to each side of the equation.
20 + -20 + -2t = -5 + -20

Combine like terms: 20 + -20 = 0
0 + -2t = -5 + -20
-2t = -5 + -20

Combine like terms: -5 + -20 = -25
-2t = -25

Divide each side by '-2'.
t = 12.5

Simplifying
t = 12.5

See similar equations:

| 8y^2-12y= | | 8x-9-3x+20=1 | | 7(-4-8/3x)/5 | | 1(2)-3y=9 | | -3(6v-7)=93 | | D/.25=-.6 | | cos(22)=x/11 | | 17-3x-5=8x-7x | | 1(1)-3y=9 | | -.546=log(x/0.3) | | 4x-1=8x+5 | | 1(0)-3y=9 | | 8n+5n^2= | | 7(-4-8/3)/5 | | 1(-2)-3y=9 | | 1/2x-6y=7 | | (a+8)(a^2-8a+64)=0 | | -115-10x=x+94 | | 5x+2=67.5 | | 21.76=3.2k | | 180=4x+148+8x+260 | | -110=-5(4+6n) | | 180=8x+32+4x+16 | | -8r-1=9r+50 | | 25x^2-10x^3= | | 180=2x+150+5x+121 | | 6x+3-9x=-6 | | 5t=-120 | | 6x+36=2x+60 | | 4/7÷5/9 | | 4y^2-0x-.9=0 | | Y=200(.75)t |

Equations solver categories